Notoginseng Triterpenes Inhibited Autophagy in Random Flaps via the Beclin-1/VPS34/LC3 Signaling Pathway to Improve Tissue Survival - Huang, Zhiyang; Luo, Xiaobin; Zhang, Yifan; Ying, Yibo; Cai, Xiong; Lu, Wenjie; Zhao, Juan; Wang, Yutian; Lin, Wenwei; Tu, Yurong; Xiang, Ziyue; Wu, Qiuji; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Random flap is widely used in surgical tissue reconstruction due to the lack of vascular axial limitation. However, the distal end of the flap is prone to necrosis due to lack of blood supply. Notoginseng triterpenes (NT) are the active components extracted from panax notoginseng, which can reduce oxygen consumption and improve the body's tolerance to hypoxia, but their role in random flaps survival has not been elucidated. In this study, we used mouse random skin flap model to verify that NT can promote cell proliferation and migration and increase blood perfusion can effectively increase the survival area of skin flap. Our study also showed that autophagy of random flaps after NT treatment was activated through beclin-1 /VPS34/LC3 signaling pathway, and the therapeutic effect of NT significantly decreased after autophagy was inhibited by 3MA. In conclusion, we demonstrate that NT can significantly improve the survival rate of random flaps through beclin-1 /VPS34/LC3 signaling pathway, which may be a promising clinical treatmen